Hematology and Iron Status Evaluation Based on Donation Characteristics in Dr. Sardjito Hospital, Yogyakarta - Fuad Anshori; Tri Ratnaningsih; Teguh Triyono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Blood donation will reduce iron storage in the body. A high frequency of donations and short interval inter-donations may increase the risk of iron deficiency. In Indonesia, detection of iron deficiency in blood donors is not a routine procedure. Therefore, the comparison of hematology and iron status based on donor characteristics is not widely known. For a month, this study was a cross-sectional study conducted at the Blood Transfusion Service Unit, Dr. Sardjito Hospital. Subjects were routine blood donors who met the criteria for donor selection; however, subjects were excluded if the CRP level was > 10 g/L and had a history of iron supplementation. Subjects were divided based on donation frequency and blood donation interval. The Kruskal-Wallis test was used to compare variables among groups with a statistical significance of p < 0.05. This study involved 145 subjects who met the criteria. Blood donations more than 20 times showed the lowest ferritin levels and iron saturation (16.9 ng/mL and 15.08%). Ferritin levels were also increased in line with the donation interval (35.5 ng/mL; 75.3 ng/mL; 92.7 ng/mL every three months). However, the hematological parameters and iron saturation did not differ significantly based on the donation interval. Hematological parameters are easy and fast procedures but have limitations in the early detection of iron deficiency. Serum ferritin has higher specificity, but its level is affected by inflammatory conditions. Ferritin levels were consistently at the lowest level in the subjects with the highest risk of iron deficiency compared to hematologic and iron saturation parameters.